Enforcing Broken Promises In Equity: Estoppel In Australia, Malaysia And Beyond - Edelman, James (Journal of Malaysian and Comparative Law, 1999)
The doctrine of estoppel has been one of the most discussed and debated doctrines for decades. One of the biggest issues for a long time was whether the doctrine could be used as a ’sword’, or cause of action, or simply as a ’shield’, a procedural device preventing a plaintiff from asserting certain facts. This debate first passed into history in Australia in 1988. But the resolution of the issue of whether estoppel could operate as a cause of action raised many new questions. As a cause of action where does estoppel belong in a taxanomy of obligations? What are the elements required in order to make out this estoppel? And what should the responses be to such a cause of action?